The hair scare - Fisher, Jeff 1952- (Bloomsbury Children's books, 2006)
A very creative child prodigy haircutter named Radbert triumphs over a king who is not very pleased with his new hairdo
Keywords: Beauty operators / Pictorial works / Juvenile fiction